Leveraging the Rice Value Chain for Poverty Reduction in Cambodia, Lao PDR, and Myanmar - World Bank Group (World Bank, Washington, DC, 2016)
Rice is an important agricultural product and food staple in the Greater Mekong Subregion (GMS), especially for its three low-income members – Cambodia, Lao PDR, and Myanmar. These countries are net exporters of rice, similar to their more advanced neighbors, Thailand and Vietnam, but their rice sector potential is still largely underutilized. They adopt slightly different approaches to rice sector development in terms of the role of the private sector, openness to foreign direct investments (FDI), and commitment to open trade, yet they all aim to remain competitive on export markets and to leverage this competitiveness for poverty reduction and boosted shared prosperity, while achieving other development outcomes such as better nutrition, climate-smart agriculture, and job creation. Cambodia, Lao PDR, and Myanmar are the ‘target countries’ of this report, while Thailand and Vietnam are the peers used for comparison and experience-sharing throughout the report. This report presents a summary of main findings, lessons learned, and policy recommendations from these workshops. The spectrum of discussions was broad, depending on the interest of each country to learn specific experiences from other countries or from the region and the world. Most workshops brought together private and public sector representatives to facilitate open dialogue and better integrate private sector objectives into agricultural strategies and policies.